Young voters: trends and preferences in the new political landscape / Nazni Noordin...[et al.] - Noordin, Nazni; Mohamed Sawal, Mohd Zool Hilmie; Zakaria, Zaherawati; Hussin, Zaliha; Shaharudin, Mohd Rizaimy; Ishak, Hadzli; Ibrahim, Syazliyati (2010)
The 12th General Election in March 2008 had changed Malaysia’s political landscape in significant ways. A series of unexpected events happened and for the first time in history, the ruling party, Barisan Nasional (BN) failed to obtain the two third majority votes. This ‘political tsunami’ had influenced people from various backgrounds especially those in the political parties to probe further into the reasons behind the changes. After a series of ‘post mortem’ and discussions, political leaders now began to realise about the importance of moving out from their ‘comfort zone’ and responding immediately to the signals from the public. By ignoring people’s voice particularly the young voters who made up more than forty percent of the total voters, political parties were digging their own graves. Thus, this paper was written in order to identify young voters’ trends and preferences in choosing their candidates to represent them in the new political landscape. The findings of this research showed that young voters preferred to choose candidates based on their profile, images and personal characteristics, visions and missions as well educational backgrounds. Most importantly, the candidates must also be ‘clean’ in all aspects. Hopefully, the findings will provide political parties better understanding of the young voters’ needs and wants in order to ensure their parties’ survival since this group of voters is the deciding factor of the future Malaysian political landscape.